The Spaces of Sekaten: Contesting Islamic Values and Market Logic in the Ritual Landscape of Surakarta, Indonesia: - - Mukhlis Anton Nugroho; Bambang Sunarto; Budi Setiyono (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
Sekaten is a Javanese Islamic ritual that was originally designed as a medium of da‘wah, integrating Islamic teachings with local cultural expressions through music, symbols, and ceremonial spaces. While Sekaten is also celebrated in other Javanese courts such as Yogyakarta, the Surakarta version displays a distinctive spatial configuration in which the royal square is dominated by a large-scale commercial night market and its ritual sites are more sharply separated between sacred and profane functions. This study aims to explore the segmentation of space within the contemporary Sekaten ritual in Surakarta and to analyze the shift from its religious orientation toward a celebratory, commodified form. Employing a qualitative descriptive method, data were collected through field observation, in-depth interviews, and literature study. The findings reveal a spatial triad in the current ritual configuration: the courtyard of the Great Mosque functions as a site for symbolic Islamic da‘wah, the mosque interior serves as a contemplative spiritual space, and the royal square (alun-alun) has evolved into a festive marketplace. This spatial segmentation reflects a broader shift in public perception—where once the ritual emphasized spiritual reflection, it is now increasingly viewed as entertainment and economic spectacle. The study concludes that reinvigorating the ritual’s spiritual dimensions is essential to preserving Sekaten’s identity as a cultural heritage of Javanese Islam amidst the forces of secularization and market commodification.